Analisis Sistem Informasi yang Sedang Berjalan dan Rencana Proyek E-Procurement dengan Pendekatan Metode New Information Economics - Idris Gautama So; Devy Listisari Saputri (Binus Business Review, 2010)
PT PLN (Persero) is a state owned which manages the biggest electricity businesses that cover the entire territory of Indonesia. His position is very potential for the Indonesian public life requires that PLN is able to manage the investment means the supply of electricity to customers. This is done with the information systems that support business processes in the body of PLN. PT PLN (Persero) has some application systems, infrastructure, service, and management used to increase the ability of the company. In PLN, there is an application that is capable of supporting PLN to conduct the procurement process is procurement information system (e-procurement). PSI Sub-party service providers as e-procurement to see investment information system (SI) and Information Technology (IT) which is proportional to the amount issued benefits and bottom-line impact for companies and can find out the level of funds / investment budgets and alignment of Information Technology there is a project in accordance with company requirements. Those needs based on business needs and applications currently running in the intersection so as to project better. Based on this, the author proposes to analyze the benefits of information technology investments by using the method of New Information Economics (NIE) that combines the two approaches both financial and non-financial. In the method NIE (New Information Economics) will be used four of the five practices that NIE Strategic Demand / Supply Planning, Innovation, Prioritization, and Alignment. The results are expected to help the company to allocate investments SI / IT is more appropriate and supports the company's performance, especially in providing added value to the parties concerned.